2023
DOI: 10.1101/2023.02.15.528679
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amygdala AVPR1A mediates susceptibility to chronic social isolation in females

Abstract: Females are more sensitive to social exclusion, which could contribute to their heightened susceptibility to anxiety disorders. Chronic social isolation stress (CSIS) for at least 7 weeks after puberty induces anxiety-related behavioral adaptations in female mice. Here, we show that Arginine vasopressin receptor 1a (Avpr1a)-expressing neurons in the central nucleus of the amygdala (CeA) mediate these sex-specific effects, in part, via projections to the caudate putamen. Loss of function studies demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 122 publications
0
1
0
Order By: Relevance
“…AVP axons project sparsely to the lateral septum, AHN, BNST, VLPO, MPOA, MPN, PeVN, LHb, LH, VMH, PH, and SON. A recent study also identified monosynaptic projections from a small number of SCN AVP neurons to the central amygdala [ 121 ]. Axons from PK2 neurons project prominently to the lateral septum, MPOA, OVLT, PVN, LH, and periaqueductal gray.…”
Section: Outputs From the Scn: Efferent Projectionsmentioning
confidence: 99%
“…AVP axons project sparsely to the lateral septum, AHN, BNST, VLPO, MPOA, MPN, PeVN, LHb, LH, VMH, PH, and SON. A recent study also identified monosynaptic projections from a small number of SCN AVP neurons to the central amygdala [ 121 ]. Axons from PK2 neurons project prominently to the lateral septum, MPOA, OVLT, PVN, LH, and periaqueductal gray.…”
Section: Outputs From the Scn: Efferent Projectionsmentioning
confidence: 99%